2005
DOI: 10.1103/physrevb.71.144504
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic vortex channeling inYBa2Cu3O7δthin films with

Abstract: Scanning Hall probe microscopy has been used to make a microscopic study of flux structures and dynamics in yttrium barium copper oxide thin-film disks containing a regular 10-m-period square array of 2.5-m-sized holes ͑antidots͒. Images obtained after field cooling the sample to 77 K in very low fields reveal that the holes can trap two flux quanta at this temperature. Scans obtained after zero-field cooling ͑ZFC͒ to 77 K and a subsequent applied field cycle clearly display preferential flux channeling along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…Similarly, a periodic arrangement of antidots can cause effective flux drainage of a sample in the descending branch of a magnetic field ramp. 25 It was also found that when the antidot lattice breaks the symmetry of the overall sample shape, or when the antidots have nontrivial shapes, the critical current density can become anisotropic 3,26 and the flux motion can be enhanced in unexpected directions. 27 Whereas superconducting films containing complex arrangements of antidots can today be readily produced using, for example, optical lithography, the theoretical modeling of the local and global features of the flux dynamics in such systems is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a periodic arrangement of antidots can cause effective flux drainage of a sample in the descending branch of a magnetic field ramp. 25 It was also found that when the antidot lattice breaks the symmetry of the overall sample shape, or when the antidots have nontrivial shapes, the critical current density can become anisotropic 3,26 and the flux motion can be enhanced in unexpected directions. 27 Whereas superconducting films containing complex arrangements of antidots can today be readily produced using, for example, optical lithography, the theoretical modeling of the local and global features of the flux dynamics in such systems is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…It has been measured in [21] that increasing the hole diameter by a factor of 2 results in a magnetization drop of ∼ 80%. In the particular limit of YBCO thin films of rectangular shape with microscopic holes, the Bean critical state has also been simulated in [22]. However, to our knowledge, none of these previous works has studied the influence of the hole pattern on the magnetization drop.…”
Section: Introductionmentioning
confidence: 99%
“…In this work the influence of isotropic pointlike disorder on the guiding of vortices was discussed for the first time. Later on, lithographic techniques have been routinely employed to create periodic pinning arrays consisting of practically identical nanostructures in the form of, e.g, microholes [20,21], magnetic dots [22], and stripes [23]. The main idea all these works share is to suppress periodically the superconducting order parameter.…”
Section: Experimental Systems With a Washboard Pinning Potentialmentioning
confidence: 99%
“…With regard to a theoretical description it has to be stated that a full and exact account of the nonlinear vortex dynamics in superconducting devices proposed in these works [20][21][22][23] in a wide range of external parameters is not available due to the complexity of the periodic PP used in these references. Due to this reason it has been proposed by the authors in a number of articles to study a simpler case, such as a WPP periodic in one direction [12,[24][25][26][27] or bianisotropic [28].…”
Section: Experimental Systems With a Washboard Pinning Potentialmentioning
confidence: 99%